Dutch White Trash: A Phoenix Without Ashes. What Happened to the Emperor’s Old Clothes? - Rogier I.C. Baart; Bart Jansen; Martine Bosman (Yuridika, 2019)
In the Dutch capitalistic consumer society, things are not made to stand the test of time, but to be replaced by other things within the foreseeable future. They are made to be thrown away, and quite often as quickly as possible, because it is this characteristic that guarantees a new purchase. In this contribution the authors will focus on a white T-shirt. The main questions are: What is the current practice in the Netherlands regarding the disposal, separation, reusing, and recycling of this Dutch white trash and how does the legal framework regulate the matter of RMG waste?.